Contribution of soil organisms to the sustainability and productivity cropping systems in the tropics - Sanginga, N.; Mulongoy, K.; Swift, M. (Elsevier, 1992)
Research to identify appropriate means of sustaining tropical soil productivity has intensified during the last 2 decades and promising technologies such as minimum tillage, herbaceous and tree based systems, and improved fallows have been identified. This paper discusses the contribution of soil microorganisms to the sustainability of such cropping systems in the tropics. A favourable environment for biological activity is promoted by management practices which: (1) maintain continuous vegetational cover of the soil and extensive perennial root growth; (2) encourage the return of plant litter to the soil; (3) support a diversity of plants (preferably and including legumes) and thence of litter inputs; (4) minimize soil disturbance (e.g. by tillage). It is concluded that although the importance of biological processes for soil fertility conservation is increasingly recognise